Pengaruh Takaran Kasgot Kotoran Ayam Terhadap Pertumbuhan Dan Hasil Tanaman Selada Krop (Lactuca sativa L.) Varietas Great Alisan - Fenny Rismayanti Meilani; Rohana Abdullah; Agus Surya Mulya (Paspalum: Jurnal Ilmiah Pertanian, 2022)
Waste is exile generated from a production process that can have a negative effect onthe environment. Organic chicken manure that is produced naturally by utilizing Black Soldier Fly (BSF) larvae can produce BSF frass as organic fertilizer of good quality, environmentally friendly, which can support sustainable agriculture. Field experiments have been carried out in the Gardens of the Faculty of Agriculture, Winaya Mukti University, Tanjungsari District, Sumedang Regency. The purpose of the study was to determine the effect of the dose of chicken manure on the growth and yield of lettuce. The design used was a randomized block design consisting of 6 treatments, namely A = 0 tons ha-1, B= 3 tons ha-1 cow manure, C= 1.5 tons ha-1 BSF of chicken manure, D = 3 tons ha-1 , E = 4.5 ton ha -1 and F = 6 ton ha-1 and repeated 4 times. The results showed that the use of chicken manure BSF frass had a significant effect on growth in plant height, the number of leaves, and root volume, and lettuce yields had a significant effect on plant fresh weight, fresh weight per plot, root fresh weight, plant dry weight, root dry weight, and root loss ratio. At the dose of 6 tons ha-1 chicken manure cassava showed the best results on plant height, the number of leaves, fresh weight of each plant, fresh weight of each plot, plant dry weight, root dry weight, and root loss ratio.